(untitled) (Hoboken, N.J., 2011)
This book introduces the methodology for collection and identification of herbal materials, extraction and isolation of compounds from herbs, in vitro bioassay, in vivo animal test, toxicology, and clinical trials of herbal research. To fully understand and make the best use of herbal medicines requires the close combination of chemistry, biochemistry, biology, pharmacology, and clinical science. Although there are many books about traditional medicines research, they mostly focus on either chemical or pharmacological study results of certain plants. This book, however, covers the systematic study and analysis of herbal medicines in general – including chemical isolation and identification, bioassay and mechanism study, pharmacological experiment, and quality control of the raw plant material and end products.
Thử nghiệm sinh học
Keywords: Plants, Medicinal,Thực vật, Thuốc; Chemistry,Hóa học